Dorsal Root Ganglia Coactivator-associated Arginine Methyltransferase 1 Contributes to Peripheral Nerve Injury-induced Pain Hypersensitivities. (1st December 2018) - Mo, Kai; Xu, Huali; Gong, Hualei; Lei, Hongyi; Wang, Yongwei; Guo, Wenjing; Xu, Shiyuan; Tu, Weifeng
Highlights: Peripheral nerve injury upregulated neuronal CARM1 expression in injured DRGs. siRNA-mediated CARM1 silencing attenuated both the development and maintenance of neuropathic pain. Pharmacological CARM1 blockade mitigated existing neuropathic pain. Abstract: Neuropathic pain is associated with gene expression changes within the dorsal root ganglion (DRG) after peripheral nerve injury, which involves epigenetic mechanisms. Coactivator-associated arginine methyltransferase 1 (CARM1), an epigenetic activator, regulates gene transcriptional activity by protein posttranslational modifications. However, whether CARM1 plays an essential role in the development and maintenance of neuropathic pain is unknown. We report here that peripheral nerve injury induced the upregulation of the mRNA and protein expression of CARM1 in the injured DRG, and blocking its expression through small interfering RNA (siRNA) in the injured DRG attenuated the development and maintenance of neuropathic pain. Furthermore, pharmacological inhibition of CARM1 mitigated peripheral nerve injury-induced mechanical allodynia and thermal hyperalgesia. Given that CARM1 inhibition or knockdown attenuated the induction and maintenance of neuropathic pain after peripheral nerve injury, our findings suggest that CARM1 may serve as a promising therapeutic target for neuropathic pain treatment in clinical applications.